From medical image to 3D entities creation - Diogo, Sara Garcia (2013)
For the generation of a FE mesh, segmentation of 2D medical images is necessary. In this work, the two main regions of the Intervertebral Disc – i.e. the Nucleus Pulposus and the Annulus Fibrosus – were the structures taking in consideration for image segmentation. A set of different algorithms and filters were used, together with a commercial software, and its results presented and discussed.